Methods of forming the creative competence of the future engineer - Dimitrova-Burlayenko, S. D. (Publishing house Education and Science, 2018)
The article deals with the process of creative training of students of technical specialties. The positions of modern scientists to determine the factors that contribute to the manifestation of creativity in the process of activity have been analyzed. Pedagogical conditions influencing preparation of students of technical universities for revealing creative competence have been determined. The methods of introducing certain pedagogical conditions into the educational process of the higher technical educational institution have been presented. Examples of educational technologies aimed at forming the creative competence of future engineers have been given.
Keywords: creativity; creative competence; students of technical universities; preparation for identification of creative competence